Planejamento financeiro para projeto de vida: uma proposta de ensino-aprendizagem com foco em estudantes finalistas do ensino médio - Kettle, Luciana do Nascimento (2022)
In the context of High School, the Common National Curricular Base - BNCC recommends that the school directs students to build a Life Project, which aims at personal and social development, through the consolidation of knowledge, representations and values that will affect their decision-making processes throughout life. In addition, the BNCC guides the teaching of financial education as a cross-cutting theme, as a way to, among other possibilities, assist students in developing a Financial Planning that enables them to achieve their dreams and goals. Given the recent implementation of the BNCC for High School (December 2018), we found in the literature the need to invest effort in designing teaching approaches that promote the convergence of Financial Planning to the Life Project. Given this problematic, this research work aimed to design a teaching-learning proposal for Financial Planning with a focus on Life Project for senior high school students. This proposal was materialized in a digital portal, called "Tô com Planos" (https://www.tocomplanos.com.br), which integrates content, organized by modules (Work and Income, Economy and Finances) and a process called Life Project Canvas. There is also a navigation guide that guides teachers and students in exploring the resources available on the portal. The research is qualitative in nature and was organized in three stages: research, implementation, and evaluation. The latter was inspired in the Delphi Method, and its purpose was to evaluate the educational product in the light of two dimensions - Resolution that the product can enable and Elaboration and Synthesis. The evaluation was carried out by a committee of experts composed of high school teachers from the state public school system and researchers. In the dimension Resolution, which refers to the degree to which the product fits or meets the needs of the problematic situation, the evaluators indicated agreement about the relevance of the product. In the dimension Elaboration and synthesis, which refers to how much the product combines a set of different elements. the evaluators also pointed out suggestions for improvement in the product, with the inclusion of some contents and themes, which were attended to and implemented in the final version of the product. These results offer indications that the educational product has the potential to contribute to the teaching-learning of Financial Planning for Life Project for senior high school students.